The Digital Landscape of Higher Education: Unpacking the Influence of Social Media on Student Academic Life - Usman Rufai Fakai; Abubakar Aliyu; Bello Abdullahi; Junaidu Yusuf (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This study explores the pervasive impact of social media on the academic pursuits of college students. Employing a descriptive survey approach, the research investigates various aspects of social media usage among students, encompassing communication and educational activities. Through the analysis of survey responses, the study examines how students allocate their time on social media platforms and its potential effects on their academic performance. The results reveal a nuanced relationship between social media engagement and academic outcomes, uncovering both positive and negative impacts. While social media offers convenience and connectivity, concerns arise regarding its addictive nature and potential distractions from academic endeavors. The paper concludes with a comprehensive set of recommendations for both institutions and students to manage the complex interplay between social media and academic success. These recommendations include implementing structured time management techniques, nurturing digital literacy skills, providing support for balancing online and offline activities, advocating for educational content utilization on social media platforms, and promoting responsible online conduct. Furthermore, the paper calls for collaboration among educational institutions, policymakers, and technology firms to formulate guidelines and policies that encourage healthy social media use while prioritizing academic goals.